Advances in Automated Valuation Modeling AVM After the Non-Agency Mortgage Crisis - d'Amato, Maurizio; Kauko, Tom (Studies in Systems, Decision and Control, 2017)
This book addresses several problems related to automated valuation methodologies (AVM). Following the non-agency mortgage crisis, it offers a variety of approaches to improve the efficiency and quality of an automated valuation methodology (AVM) dealing with emerging problems and different contexts. Spatial issue, evolution of AVM standards, multilevel models, fuzzy and rough set applications and quantitative methods to define comparables are just some of the topics discussed.